The Effect of Applying the Discovery Learning Model on Students’ Civic Knowledge in the Civics Subject in Grade IV at SD Negeri Tidung, Makassar - Muthmainnah, St.; AP, Nurfaizah; Aras, Latri (International Journal of Elementary School Teacher, 2024)
This study aims to determine the description of the application of the Discovery Learning model, to know the description of civic knowledge and to determine the effect of the application of the Discovery Learning Model on students' civic knowledge in Civics Subjects in Class IV SD Negeri Tidung Makassar. This research is a study that uses a quantitative approach with the type of experimental research and the design used is a non-equivalent control group design and a form of Quasi Experimental. The type of sampling technique used is purposive sampling with a sample size of 40 students. The data results in this study are the results of the pretest and posttest. Data analysis techniques are descriptive data analysis and inferential data analysis. Descriptive statistical results obtained from learning outcomes on student civic knowledge material. The results of the analysis using the independent sample t-test showed that the tested results were smaller than 0.05, namely 0.000 <0.05. Sig. (2-tailed) < 0.05 or 0.000 < 0.05 which means H_0 is rejected and H_1 is accepted. Thus it can be concluded that the discovery learning model affects the civic knowledge of fourth grade students of SD Negeri Tidung Makassar.